Herramientas de Inteligencia Artificial en los Procesos Proyectuales Arquitectónicos, caso de estudio: Residencia Universitaria en el cantón Ambato - Álvarez Quezada, Salomé Alexandra (2024)
The influence of Artificial Intelligence (AI) tools in architectural design processes is crucial for the evolution of design and construction. These tools offer optimization capabilities that can enhance the efficiency of results. In the context of the University Residence in Ambato canton, the application of AI in architectural design processes can achieve optimal results in a reduced timeframe. The problem lies in the lack of efficiency in the results of architectural projects, which generates the need to analyze how AI tools can influence the architectural design process of design and construction companies, specifically in the University Residence of Ambato canton. The objective is to investigate how these tools can be used at each stage of the architectural design process, from conceptualization to final delivery to the client, to optimize the design of the University Residence. A qualitative study will be carried out through exploratory and comparative bibliographic research. Collection and documentary analysis techniques will be used to achieve the first objective and create a solid foundation for the research. Observation and interviews will be conducted with the users of the University Residence and the professionals involved in its design and measurement to achieve the second objective and obtain a thorough diagnosis of the University Residence. The proposal involves analyzing the influence of Artificial Intelligence tools in the architectural design process of the University Residence in Ambato. This includes the use of generative algorithms to explore and optimize the design process, covering conceptualization, functionality, volumetrics, and architectural visualization. Additionally, it is necessary to identify and apply the AI tools required to achieve the overall research objective.